ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PROFITABILITAS PADA PT BANK MANDIRI (Persero) TBK YANG TERCATAT DI BURSA EFEK INDONESIA - Hikma Niar (AkMen JURNAL ILMIAH, 2016)
This research aimed to analyze the influence of Loan to Deposit Ratio (LDR), Non Performing Loan (NPL) and the Capital Adequacy Ratio (CAR) simultaneously on Return On Assets (ROA) Loan to Deposit Ratio (LDR) to Return On Assets (ROA), Non Performing Loan (NPL) on Return on Assets (ROA), Capital Adequacy Ratio (CAR) on Return on Assets (ROA) at PT. Mandiri Bank. The results showed variable LDR, NPL and CAR simultaneously significant effect on ROA. That is, any change in the independent variable, namely LDR, NPL and CAR simultaneously or together will affect the ROA. Variable Loan to Deposit Ratio (LDR) and no significant positive effect on Return On Assets (ROA), variable Non Performing Loan (NPL) and significant negative effect on Return On Assets (ROA) .Variabel Capital Adequacy Ratio (CAR) and the positive effect significantly to Return on Assets (ROA) at Bank Mandiri (Persero) Tbk. The most dominant variable partially on Return On Assets (ROA) is variable Non Performing Loan (NPL) and Variable Capital Adequacy Ratio (CAR) .Variabel NPL and significant negative effect on Return On Assets (ROA) and variable positive and significant effect CAR on Return on Assets (ROA).